An Integrated Cuckoo AES Key Generationapproach with Bilinear Pairing to Detect Malicious Third-Party Auditors in the Cloud (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To handle huge amounts of data, either a single user or organization are dependingon the cloud environment but security to their data is the major concern that the cloud serviceprovider has to take care of in the public clouds during the process of outsourcing. So, thecloud environments have deployed a component known as “Third Party Auditor”, whichverifies the data in the cloud and ensures that the data is not tampered with by the attackers.While interacting with the public cloud, every user has a period known as the “verificationperiod”, during which the user can raise the data challenge task to the auditor. In general, thedata uploaded by the user are divided into various blocks or segments. Hence, to verify asingle user data the auditors have to generate multiple integrity reports and should check theirconsistency. If TPA detects any inconsistent data, then it has the right to reject the processand notifies the same user but the major problem is TPA works simultaneously with moreusers because of which the verification process becomes a burden to the TPA. If the system isoverloaded with more verification requests then the cost of computing in the cloud increasesand the time to check the data integrity also increases which results in compromise by theTPA. So, to address this issue many researchers have proposed integrity verificationalgorithms but most of them suffer from many design issues like resource allocations, relaytime decisions, and time consumption hence the proposed system has implementeda cuckooalgorithm integrated with AES to generate the keys and performs bilinear map functions torepair and audit within an optimal time